Effect of Combined ST36 (Zusanli) and SP6 (Sanyinjiao) Acupoint Stimulation on Appetite in Preschool Children - Dewi Kartika Sari; Yuninda Loviana Ersianti; Fredlina Rossa Balindra (Universitas Muhammadiyah Malang, 2026)
Background: Appetite problems in preschool children can negatively affect nutritional intake and growth and remain a public health concern. Conventional interventions are often insufficient, highlighting the need for alternative approaches. Acupressure is considered a safe, practical, and potentially effective method to improve appetite. Objective: This study aimed to determine the effect of acupressure at ST36 (Zusanli) and SP6 (Sanyinjiao) on appetite in preschool children. Methods: This quasi-experimental study with a pretest–posttest control group design involved 40 preschool children. The intervention group received daily acupressure for two weeks, while the control group received education. Appetite was measured using the Early Child Appetite and Satiety Questionnaire. Data were analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U test with a significance level of α ≤ 0.05. Results: Both groups showed significant improvements (p < 0.001), with greater improvement observed in the intervention group. The between-group analysis also showed a significant difference (p = 0.037), indicating that acupressure had a stronger effect compared to education alone. Conclusion: Acupressure at ST36 and SP6 is effective in improving appetite in preschool children and can be considered a feasible non-pharmacological intervention.